FRASA NOMINAL BAHASA MOI - Siti Masitha Iribaram (Balai Bahasa Provinsi Papua, 2019)
This paper discusses about nominal phrase of Moi language. Nominal phrase is the phrase that has distribution like as noun. The purpose of this paper is to describe nominal phrase pattern of Moi language, classification of word classes and its structure. This paper uses descriptive method by three steps, that is to collect data, to analyze data, and to describe data. Its collecting data uses the conversation method by provocative technique as basic technique and face to face technique, and note technique as the next technique. Analyzing of data uses distributional method. General pattern of nominal phrase in Moi language is DM. Nominal phrase of Moi language is consist of core constituent that has noun as its content and attribute constituent that has noun, pronoun, adjective, definite article, numeral, and relative clause. Some of meaning relation was happened as the result of this syntactic process, it is to state possessive, locative, qualitative, quantitative, deictic, and descriptive.